1992
DOI: 10.1007/bf02053762
|View full text |Cite
|
Sign up to set email alerts
|

Sutureless laparoscopic rectopexy for procidentia

Abstract: Procedures for treating rectal prolapse may constitute some of the best applications for colorectal laparoscopic techniques. Although the condition is benign, rectal prolapse is often debilitating and frequently progressive in terms of functional limitations. Moreover, many patients are elderly, medically unfit, or both. A technique that afforded relief of prolapse and of incontinence by laparoscopic rectal sacropexy, performed without sutures, using a newly designed laparoscopic sacral tacker and laparoscopic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
1
5

Year Published

1995
1995
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(49 citation statements)
references
References 1 publication
1
42
1
5
Order By: Relevance
“…In addition Hill et al [5] have reported the use of the endoscopic hernia stapler to control presacral hemorrhage in open rectal surgery. Berman et al described similar techniques employing laparoscopic sacral tacker and laparoscopic staplers to fix the mesh to the sacrum and rectum [1]. Laparoscopic sacral tackers have the obvious advantage of being hemostatic; however, we feel the mesh is best sutured to the side wall of the rectum.…”
Section: Discussionmentioning
confidence: 99%
“…In addition Hill et al [5] have reported the use of the endoscopic hernia stapler to control presacral hemorrhage in open rectal surgery. Berman et al described similar techniques employing laparoscopic sacral tacker and laparoscopic staplers to fix the mesh to the sacrum and rectum [1]. Laparoscopic sacral tackers have the obvious advantage of being hemostatic; however, we feel the mesh is best sutured to the side wall of the rectum.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is currently no established consensus as to the best surgical treatment, a laparoscopic approach to rectal prolapse repair has become increasingly popular ever since its description in 1992 [8]. Several studies have shown the benefits of laparoscopy when compared to open rectopexy (OR) [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, a perineal approach has been considered the operation of choice in any elderly or high-risk patient, because it was associated with lower perioperative morbidity, decreased pain, and a shorter length of hospital stay [6]. However, advances in minimally invasive techniques have called into question the optimal procedure for rectal prolapse, especially when considering long-term outcomes such as recurrence or anorectal function [7].Although there is currently no established consensus as to the best surgical treatment, a laparoscopic approach to rectal prolapse repair has become increasingly popular ever since its description in 1992 [8]. Several studies have shown the benefits of laparoscopy when compared to open rectopexy (OR) [9,10].…”
mentioning
confidence: 99%
“…After the first results of laparoscopic rectopexy [3, 4], minimally invasive surgery for rectal prolapse has been performed with increasing frequency.…”
Section: Introductionmentioning
confidence: 99%